Forestalling the Epidemics of Parkinson's Disease Through Plant-Based Remedies - Banjari, Ines; Marček, Tihana; Tomić, Svetlana; Waisundara, Viduranga Y. (Frontiers in Nutrition, 2018)
among individuals as well as economies worldwide. The main characteristics of PD is a progressive loss of dopaminergic neurons resulting in the loss of motor function, in non-motor symptoms, and in cognitive decline. Similar to many other chronic diseases, complementary and alternative therapies (CAT) are very popular for the treatment of this disease. This review evaluates six plants, three from European and Asian traditional medicinal systems: (1) Atropa belladonna, (2) Hyoscyamus niger, (3) Lepidium meyenii, (4) Aspargus racemosus, (5) Mucuna pruriens L., and (6) Gingko biloba. Atropa belladona and Hyoscyamus niger in particular, are better known for their poisonous and narcotic effects than as potentially effective plants for the treatment of neurodegenerative diseases. Ginkgo biloba is one of the most widely cultured plants in Traditional Chinese Medicine with high antioxidant potential which contributes to its neuroprotective/ anti-apoptotic activity. The bioactive compounds, anti-neurodegenerative effects and other neuroprotective effects of all six plants are discussed herein.